Shoulder kinetics of vaulters during pole bending in the pole vault: focus on relationships with isokinetic shoulder strength - Kageyuki, T.; Kigoshi, K.; Yokozawa, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2025)
The purpose of this study was to investigate the relationships between the shoulder kinetics of pole vaulters during pole bending and the isokinetic strength of the shoulder, and to clarify characteristics of the shoulder kinetics. The three-dimensional coordinates of the vaulters' body landmarks were recorded using a motion-capture system. The box reaction force was measured using a force plate placed under the planting box. The joint force and joint torque acting on a hypothetical shoulder joint were estimated using inverse dynamics calculations for a synthetic upper limb segment, assuming both upper limbs to be a single segment. The pole bending phase was divided into three sub-phases, the "take-off," "drive," and "swing," in order to determine unique characteristics of shoulder kinetics during vaulting. Isokinetic tests were conducted to measure shoulder strength.